Pengaruh Literasi Keuangan, Toleransi Risiko, dan Overconfidence Terhadap Keputusan Investasi Saham: Studi pada Mahasiswa di Surabaya - Amelia Fandiarta; R. A. Sista Paramita (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the influence of financial literacy, risk tolerance, and overconfidence on stock investment decisions among university students in Surabaya. The study used a quantitative approach with an associative explanatory design. Data were obtained through questionnaires distributed to 231 university students with stock investment experience. Respondents were selected using purposive sampling followed by snowball sampling. The collected data were analyzed using multiple linear regression with the aid of SPSS software. The results showed that financial literacy and risk tolerance had a positive and significant effect on stock investment decisions. In addition, overconfidence also had a significant effect, indicating that psychological factors also influence investment decision-making behavior. This study is limited by the scope of respondents, which only involved university students in Surabaya, so the results cannot be widely generalized. Therefore, further research is recommended to expand the research object and add other variables, such as financial technology or investment experience. The findings of this study emphasize the importance of improving financial literacy and understanding investor risk profiles in supporting the quality of investment decisions, especially for young investors.